Geomorphological specific features of Trebinje as tourist attraction - Vukojević Dajana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2011)
The municipality of Trebinje is located in the Trebišnjica river basin in the south of Bosnia and Herzegovina. Among Bileća, Ljubinje, Ravno, Herceg Novi, Dubrovnik and Nikšić a very specific and distinguishable karst countryside has developed which is made of karst polje in a debris, mountainous scope (Leotar, Bijela Gora, Zubačke mountains) and huge number of bare limestone hills and the surfaces with all micro shapes of holokarst. The author emphasizes the tourist attractions of the specific geomorphological shapes that can be valorized by the tourists in his works.